Neuroprotective effect of phospholipase A2 from Malaysian Naja sumatrana venom against H2O2-induced cell damage and apoptosis - Abdullah, Nur Atiqah Haizum; Sainik, Nur Qisya Afifah Veronica; Esa, Ezalia; Muhamad Hendri, Nur Afrina; Ahmad Rusmili, Muhamad Rusdi; Hodgson, Wayne C.; Shaikh, Mohd Farooq; Othman, Iekhsan (Frontiers in Pharmacology, 2022)
Oxidative stress is one of the factors involved in the pathogenesis of several neurodegenerative diseases. It has been reported that a secretory phospholipase A2 known as A2-EPTxNSm1a has lower cytotoxicity in neuronal cells compared to its crude Naja sumatrana venom. In this study, A2-EPTxNSm1a was tested for its neuroprotective activity on human neuroblastoma cells (SH-SY5Y) differentiated into cholinergic neurons against oxidative stress induced by hydrogen peroxide (H2O2). H2O2 treatment alone increased the caspase-3 and caspase-8 activities, whereas pre-treatment with A2-EPTxNSm1a reduced the activity of these apoptosis-associated proteins. Moreover, A2-EPTxNSm1a protects the morphology and ultrastructure of differentiated SH-SY5Y cells in the presence of H2O2. Oxidative stress increased the number of small mitochondria. Further evaluation showed the size of mitochondria with a length below 0.25 µm in oxidative stress conditions is higher than the control group, suggesting mitochondria fragmentation. Pre-treatment with 278 A2-EPTx-NSm1a attenuated the number of mitochondria in cells with H2O2 Furthermore, A2-EPTxNSm1a altered the expression of several neuroprotein biomarkers of GDNF, IL-8, MCP-1, TIMP-1 and TNF-R1 in cells under oxidative stress induced by H2O2. These findings indicate that anti-apoptosis with mitochondria-related protection, anti-inflammatory effect, and promote expression of important markers for cell survival may underlie the neuroprotective effect of A2-EPTxNSm1a in cholinergic-rich human cells under oxidative stress, a vital role in the neuronal disorder.